Over 21.0% faradaic efficiency of ambient ammonia production: Photoelectrocatalytic activity of MOF-235 - Camargo, Luan Pereira; Silva, Paulo Rogério Catarini da; Batagin-Neto, Augusto [UNESP]; Klobukoski, Vanessa; Vidotti, Marcio; Dall'Antonia, Luiz Henrique (Elsevier, 2022)
In recent years, the Haber-Bosh process's ammonia synthesis has shown a lot of energy consumption and significant CO2 emissions. In this sense, the photoelectrochemical production of NH3 via dinitrogen fixation has been showing a promising strategy. Thus, in this work, ammonia production under photoelectrocatalytic condition was carried out using the metal-organic iron terephthalate structure (MOF-235), obtained by a simple and low-cost process (solvothermal). The results indicated greater activity for the nitrogen reduction reaction (NRR) compared to the hydrogen reduction reaction (HRR), in addition to a high yield of NH3 0.716 µg h−1 cm−2 and Faradaic efficiency greater than 21.0% at - 0.2 V vs reversible hydrogen electrode in 0.1 mol L−1 Na2SO4 electrolyte. It is believed that the good results of MOF-235 during NRR are related to a high specific area of MOF, making available active sites of trinuclear-oxocentered iron in abundance. The material homogeneity in the electrode and the excellent light absorption were also decisive factors for the supply of high energy electrons necessary for ammonia production.
Keywords: Nanoscale materials; Photoelectrocatalysis; Semiconductor; Solvothermal synthesis